ANTIOXIDANT AND FREE RADICAL SCAVENGING CAPACITY OF EXTENSIVELY USED MEDICINAL PLANT OF PUNICA GRANATUM - VINODHINI S; SHRI PREETHI M; NUSRATH FATHIMA N; SHIVANI S KUSHWAHA; Rajeswari v, Devi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present study was aimed to examine the in vitro antioxidant property and free radical scavenging capacity of Punica granatum leaves, which are widely used in the Ayurvedic treatment. Methods: Aqueous and methanol extracts were prepared and to assess for their Phytochemical analysis to find out the various compounds and total yield of phenolic and flavonoid contents by spectrophotometer methods. Free-radical scavenging capacity and antioxidant activity was estimated by using a number of chemical assays are DPPH, H2O2, FRAP, TRAP and beta carotene assay. Results: It showed that aqueous extract had greatest antioxidant activity and contained significant levels of total phenolic and flavonoids content expressed as mg of gallic acid and quercetin equivalent/g of extracts. The extracts showed antioxidant activity in vivo by protecting yeast cells against oxidative stressing agent H2O2. Conclusion: These results specified the Punica granatum is good source of natural compounds which might have benefits for health, which can be used in dietary application with a possible to reduce oxidative stress. Key words:Â Punica granatum, Free-radical scavenging capacity, phytochemical, antioxidant, yeast culture.